Courage and Heroism of Soviet Soldiers in the Battle of Kursk - V. P. Gridnev (Управленческое консультирование, 2023)
The appeal to this topic is due to the 80th anniversary of the victory at the Kursk Bulge (August 23, 2023), as well as the conduct of a special military operation. The Battle of Kursk demonstrated the morale, unity and will of the multinational Soviet people in defending their Fatherland. Only on the Kursk Bulge 248 servicemen who showed courage and heroism were awarded the high title of Hero of the Soviet Union. Their patriotism, service to the Fatherland and responsibility for its fate serve as an example for the population of the country, soldiers and officers of the Armed Forces of Russia.